GRE revised general test : inside look at the test changes effective August 1, 2011 - Educational Testing Service (New York : McGraw-Hill, 2010)
This guide is packed with everything you need to succeed on the test--and move forward toward your degree. No other guide to the GRE Revised General Test gives you: everything you need to know about the revised test, straight from the test-makers!; hundreds of authentic test questions--so you can study with the real thing; two complete tests--one in the book and one on CD-ROM; In-depth descriptions of verbal reasoning and quantitative reasoning; detailed information about the analytical writing essay tasks--with sample responses and actual rater's comments--Cover
On the cover: ETS The People who make the test!
On the cover: Test prep for all test dates on or after August 1, 2011
Includes'Official Powerprep II CD-ROM complete simulated test experience for the computer-based GRE revised general test'
Book is accompany by 1 CD entitled'The official guide to the GRE revised general test Powerprep II' bearing the same call number and available at Bahagian Koleksi Media.
System requirements for CD-ROM: Microsoft Windows 200, XP, Vista, or 7
Keywords: Graduate Record Examination -- Study guides